EVALUASI INFORMASI ONLINE PADA SITUS WEB PUSAT PERPUSTAKAAN UNIVERSITAS PAMULANG - Sri Rama Putri; Ade Julius Konyanan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The Pamulang University Library has created an official website to improve its capabilities in serving and disseminating information. However, this study shows several features that need to be addressed, such as students' lack of understanding of the website, lack of content that guides library activities, and information that is rarely updated. To overcome this problem, researchers applied the System Development Life Cycle methodology in developing a library information system. Website development involves the function of managing warehouses and returning books, as well as managing user, admin and book data. Through evaluating the performance of the user interface using the heuristic evaluation method, researchers found deficiencies in the features provided, such as translation features, changing font sizes, and live chat. These features were then successfully implemented on the Pamulang University Library Center website. Thus, this research contributes to improving service and user experience in accessing information on the university library website.